Green Purchase Intention Sumbawa University of Technology Students - Nova Adhitya Ananda; Fahlia Fahlia; Diah Intan Syahfitri (Politeknik Negeri Batam, 2020)
Green purchase intentions is consumers' interest in buying products that are not harmful to the environment. The theory of planned behavior (TPB) was used to explain the intention to buy green. The variables used to explain green purchase intention are environmental knowledge, environmental awareness, and attitude. This study used 200 respondents who were selected using a purposive sampling technique. Variant-based Structural Equation Modeling (SEM) is used as a technique in analyzing research data. From the data that has been processed, it shows that the variables of environmental knowledge and environmental concern affect green purchase intention through attitudes.